Mesoporous carbon hollow microspheres with red blood cell like morphology for efficient microwave absorption at elevated temperature. (June 2018) - Xu, Hailong; Yin, Xiaowei; Li, Minghang; Ye, Fang; Han, Meikang; Hou, Zexin; Li, Xinliang; Zhang, Litong; Cheng, Laifei
Abstract: Red blood cell like-mesoporous carbon hollow microspheres (RBC-PCHMs) have been synthesized by modified stöber method with following pyrolysis and etching procedures. The as-synthesized carbon spheres show unique red blood cell like morphology with interior void and mesoporous shell. The composite mixing phenolic resin with 10 wt. % RBC-PCHMs exhibits an efficient absorption bandwidth (reflection loss less than −10 dB,  > 90% absorption) more than 3 GHz with a sample thickness of  < 2 mm in the X band at the temperature from 300 to 523 K. The fundamental mechanism based on polarization loss and conductive loss is discussed, the polarization loss decreases with rising temperature and compensates the increase of conductive loss, which significantly contributes to impedance match at elevated temperature. Our results demonstrated that the mesoporous carbon hollow spheres with red blood cell-like morphology have great potential to be lightweight microwave absorbers at elevated temperature. Graphical abstract: Mesoporous carbon hollow spheres with red blood cell like morphology, which possesses enhanced interfacial polarization along with low crystallization degree and well impendence match at elevated temperature, exhibit excellent microwave absorption performance with a minimum reflection loss (RL) value of − 59.7 dB and effective absorption bandwidth more than 3 GHz from 300 to 523 K. Image 1